Epoxy-Barium titanate nanocomposite fabrication process and dielectric properties at S and G band - Nurulfadzilah, Hasan; Nurul Hazlina, Noordin; Mohamad Shaiful, Abdul Karim; Nurhafizah, Abu Talip Yusof; Mohd Ruzaimi, Mat Rejab (Institution of Engineering and Technology, 2022)
This paper focused on the fabrication of epoxy-barium titanate nanocomposite and its dielectric properties at S-band (2 to 4GHz) and G-band frequencies (4 to 6 GHz). The nanocomposite is fabricated by mechanically mixing the two materials and curing agent together. Then the mixture is let to cure in a controlled environment. Permittivity and loss tangent of the nanocomposites were measured using dielectric probe technique. Results show that both the permittivity and loss tangent of the nanocomposite increases as the filler content increases. The highest permittivity is achieved at 40 vol.%, which is around 16. However, agglomeration of filler particles in the matrix is a problem that must be overcome, when fabricating the nanocomposite, especially in higher filler concentration.